2001
DOI: 10.1037/0003-066x.56.9.735
|View full text |Cite
|
Sign up to set email alerts
|

American psychology's struggles with its curriculum: Should a thousand flowers bloom?

Abstract: Although discussions of a core curriculum in doctoral training in psychology can be heard in contemporary psychology, there is no such common core, nor has one ever existed in American psychology's history. Advocates of a core curriculum argue that it ensures breadth of training, an outcome made even more important by growing specialization in psychology, and that it provides psychologists with a needed common identity as members of a recognized professional discipline. Opponents argue that a core curriculum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 34 publications
1
93
0
4
Order By: Relevance
“…Afterwards they should 'typically' be able to 'continue to undertake pure and/or applied research and development at an advanced level, contributing substantially to the development of new techniques, ideas or approaches' (QAA, 2001). USA guidelines for clinical psychology programmes also emphasize both science and practice components (Benjamin, 2001; American Psychological Association (APA), 2002). The American accreditation criteria stipulate 'all programmes should enable their students to understand the value of science for the practice of psychology and the value of practice for the science of psychology' and emphasize the need for 'attention to the empirical basis for all methods involved in psychological practice ' (APA, 2002, p. 5).…”
Section: The Importance Of the Training Environmentmentioning
confidence: 98%
“…Afterwards they should 'typically' be able to 'continue to undertake pure and/or applied research and development at an advanced level, contributing substantially to the development of new techniques, ideas or approaches' (QAA, 2001). USA guidelines for clinical psychology programmes also emphasize both science and practice components (Benjamin, 2001; American Psychological Association (APA), 2002). The American accreditation criteria stipulate 'all programmes should enable their students to understand the value of science for the practice of psychology and the value of practice for the science of psychology' and emphasize the need for 'attention to the empirical basis for all methods involved in psychological practice ' (APA, 2002, p. 5).…”
Section: The Importance Of the Training Environmentmentioning
confidence: 98%
“…One element that clearly is a contributing factor is psychology's failure to define itself. As Benjamin (2001) put it, " Psychologists may have no right to expect the public to understand their psychology when there is ample evidence that psychologists have never been able to define it for themselves" (p. 736). Of course, an implication of this claim is that if we could successfully define our field, we might be justified in expecting others to comprehend, respect, and usefully apply the knowledge we have generated.…”
Section: Resultsmentioning
confidence: 97%
“…In reviewing the struggle American psychology has had with its curriculum, Benjamin (2001) observed that "Efforts over the past century to define the core elements of education and training in psychology, that is, to identify the essence of what a psychologist is, have met with little or no success" (p. 736). He concluded, "Historically, psychologists have never been either able or willing to answer the question, 'What is a psychologist?'…”
Section: Defining Psychology In the Service Of Educating Psychologistsmentioning
confidence: 98%
“…The literature is rife with models pertaining to the scientific training of psychologists (e.g., Carter, 2002;Chwalisz, 2003;Benjamin, 2001;McFall, 2002;Peterson, Peterson, Abrams, & Stricker, 1997;Stoltenberg et al, 2000;Stricker, 2002;Stricker & Trierweiler, 1995). These studies provide a context for this article by discussing the various models of clinical training and presenting the on-going debates on scientific training and practice of psychologists.…”
Section: Brief Review Of the Literaturementioning
confidence: 99%